2016
DOI: 10.1515/jvetres-2016-0064
|View full text |Cite
|
Sign up to set email alerts
|

Shewanella putrefaciens – a new opportunistic pathogen of freshwater fish

Abstract: In recent years, Shewanella putrefaciens, commonly known as a halophilic bacteria, has been associated with serious health disorders in freshwater fish. Therefore, it has been described as a new aetiological agent of the disease, named shewanellosis. S. putrefaciens is a heterogeneous group of microorganisms, belonging to the Alteromonadaceae family. Based on different criteria, three biovars and biogroups as well as four genomic groups have been distinguished. The first infections of S. putrefaciens in fish w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 38 publications
0
32
0
Order By: Relevance
“…However, S. parauberis and S. putrefaciens showed resistance or intermediate susceptibility to oxytetracycline and romet, respectively. Multidrug resistance was reported for A. veronii , S. parauberis and S. putrefaciens previously (Haines et al., ; Meng, Kanai, & Yoshikoshi, ; Nawaz et al., ; Paździor, ; Pękala et al., ). According to our anecdotal observation, fish mortality ceased completely 10 days postadministration of Aquaflor ® to catfish in the raceways at a dose of 10 mg florfenicol/kg fish/d for 10 consecutive days.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…However, S. parauberis and S. putrefaciens showed resistance or intermediate susceptibility to oxytetracycline and romet, respectively. Multidrug resistance was reported for A. veronii , S. parauberis and S. putrefaciens previously (Haines et al., ; Meng, Kanai, & Yoshikoshi, ; Nawaz et al., ; Paździor, ; Pękala et al., ). According to our anecdotal observation, fish mortality ceased completely 10 days postadministration of Aquaflor ® to catfish in the raceways at a dose of 10 mg florfenicol/kg fish/d for 10 consecutive days.…”
Section: Discussionmentioning
confidence: 74%
“…Of late, it was isolated from cultured tilapia ( Oreochromis niloticus ) from an Egyptian fish farm (El‐Barbary, ). Therefore, it has been described as a new aetiological agent of the disease, named shewanellosis, with three distinguished biovars as well as four genomovars (Paździor, ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the TH2012 T genome contains a putative prophage (Fig. ) (Wechprasit et al , ) and some virulence genes found in some Shewanella isolates (Paździor, ; Yousfi et al , ) such as putative haemolysins, chitinases and proteases (Wechprasit et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…As part of the physiological microbiota of gills and intestine, S. putrefaciens group is now considered an opportunistic aetiological agent (shewanellosis) also in fishes (Pakingking, Palma, & Usero, 2015;Paździor, 2016). The first report was on a marine fish species (rabbitfish) (Saeed, Alamoudi, & Al-Harbi, 1987).…”
mentioning
confidence: 99%
“…The first isolation related to health disorders in freshwater fishes dates back to 2004 in Poland; since then, episodes of infection have been reported in different fresh and saltwater species, including koi (Cyprinus carpio L.). Skin necrotizing and ulcerative lesions and gill necrosis are the main gross pathologic findings, and polymicrobic infections have been recorded (Altun et al, 2014;El-Barbary, 2017;Esteve, Merchán, & Alcaide, 2017;Korun, Akgun-Dar, & Yazici, 2009;Kozińska & Pękala, 2004;Paździor, 2016;Pękala et al, 2015;Qin, Zhu, & Xu, 2014;Rusev, Rusenova, Simeonov, & Stratev, 2016).…”
mentioning
confidence: 99%